Orienting to the sun improves camouflage for bilaterally symmetrical prey - William Allen (Biological Journal of the Linnean Society, 2021)
Here, we investigate the camouflage consequences of animal orientation behaviour. Shadows can be a conspicuous cue to the presence of prey. For bilaterally symmetrical animals, light field modelling indicates that camouflage will be improved when an animal orients its longitudinal axis directly towards or away from the sun, because the appearance of shadows is minimized. We test this prediction with a field predation experiment, in which wild birds hunt for artificial camouflaged prey oriented with the longitudinal axis either parallel or perpendicular to the sun. We find that prey oriented parallel to the sun are 3.93 times more likely to survive than prey oriented perpendicular to the sun. This result demonstrates the strong orientation dependence of camouflage. Given the dramatic difference in survival of prey with different orientations, we suggest that camouflage should be investigated as an important determinant of the positional behaviour of animals.